DECENTRALIZATION OF BUDGET EXPENDITURE EXECUTION AND ITS EFFECT ON MUNICIPAL SPENDING - dos Santos, Dinah Vieira; Costa, Patrícia de Souza; de Azevedo, Ricardo Rocha (Advances in Scientific and Applied Accounting, 2021)
Objective: The research aimed to investigate the effect of purchasing decentralization on municipal spending, through the theoretical lens of Public Choice Theory. Method: The analysis was developed using quantile regression performed with data obtained from an electronic questionnaire, analyzed together with data from city halls from 2013 to 2018, considering expenditures with different pressures and budget constraints. Results or Discussion: The results indicate that in areas with enough linkages, decentralization lowers spending; in areas with insufficient linkages and high social pressure, it presented the opposite result, an increase, with no effect in areas without linkages and low pressure. Through the adopted theoretical lens, the decisions in the public sector does not necessarily follow a logic of well-being, but are influenced by other factors, such as self-interest of the actors. However, the decision does not depend solely on individual aspects and can be influenced also by organizational aspects, such as the decentralization of the implementation of budget expenditure. Contributions: The results bring three contributions. First, by discussing the effect of practices that are in use in governments, often automatically, it allows for greater reflection on the decisions of the organization of these practices. Second, it draws attention to the effects caused by the budget linkage, which should be considered by the surveys, given the specificities of each linkage. Third, even when having autonomy over purchases, managers of decentralized units tend to seek efficiency only when the resources allocated to their areas are sufficient. Thus, the research suggests the existence of an effect organizational moderator in the search for maximization.